1984
DOI: 10.1007/bf01973829
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of histamine release from isolated rat mast cells: Differences when various ligands are used to induce secretion

Abstract: Differences are reported in the response of rat peritoneal mast cells to three releasing agents: ovalbumin, to which the rats were actively sensitized, anti-IgE, an immunoglobulin directed against the rat IgE molecule, and IgE chemically dimerized with suberimidate. Both the rate of histamine release and the rate of desensitization were measured for each of the three ligands. The calculated doubling times for the rates of histamine release due to ovalbumin, anti-IgE and dimer were 19.6 sec, 168 sec and 37.7 se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1985
1985
2006
2006

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…The T1/2 for inactivation by Con A (11.2 min) that we have found is considerably longer than that which has been reported (1.0 min) for antigen [26]. This agrees with the suggestions of others [27,28] that various immunologic agents may have different modes of action.…”
Section: Discussionsupporting
confidence: 88%
“…The T1/2 for inactivation by Con A (11.2 min) that we have found is considerably longer than that which has been reported (1.0 min) for antigen [26]. This agrees with the suggestions of others [27,28] that various immunologic agents may have different modes of action.…”
Section: Discussionsupporting
confidence: 88%
“…As we have previously reported [5] there are quantitative differences in the response of rat peritoneal mast cells to three different modes of cross-linking the Fc-receptor for IgE: antigen (ovalbumin), anti-IgE and dimerized IgE. Possible explanations for these differences were investigated in the work reported here.…”
Section: Discussionmentioning
confidence: 77%
“…In a previous paper [5] we reported that the rate of release due to anti-IgE was slower than that due to ovalbumin. Both agents were used at supra-maximal doses.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…These different kinetics in cal cium response may reflect a more effective cross-linking of surface antibody IgE by a multivalent ligand (mite al lergen) than by the functionally bivalent anti-human IgE. These results may be compared to the difference in the rate of release of histamine induced cither by antigen or anti-IgE in rat mast cells [30] or in human basophils [31], Indeed, the release of histamine by antigen occurs with a shorter lag period and a more rapid rate than seen with anti-IgE.…”
Section: Discussionmentioning
confidence: 99%